A retrospective analysis of nursing patients with Stevens-Johnson syndrome or toxic epidermal necrolysis - HE Xueyu; LIU Jiaqi; CHEN Rong; ZENG Xiaofang; WANG Yu; CHEN Mudiao; LIU Hongfang (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Objective To summarize and analyze the skin care methods for and outcomes of patients with Stevens-Johnson syndrome (SJS) or toxic epidermal necrolysis (TEN). Methods Inpatients with SJS or TEN at Dermatology Hospital of Southern Medical University from January 2016 to February 2023 were retrospectively analyzed. The changes in the total body surface area (BSA), control time, healing time, hospitalization days and complications of skin lesions during hospitalization were analyzed. Results Forty-one patients were included. Fourteen patients were treated with dry powder exfoliation, while 16 patients were treated with wet-dress healing care. The rest 11 cases were treated with the combination of dry powder exfoliation, moist burn ointment and vaseline gauze. On the 5th day, treatment with either dry powder exfoliation or wet-dress healing care significantly decreased the BSA (t=5.25,6.28, P<0.001). On the 9th day, the combination care also markedly decreased BSA from the baseline (t=2.03, P=0.042). There was no significant difference in the incidence of complications among the three nursing models (P=0.827). Conclusions In combination with systemic treatments, early dry powder exfoliation and later wet dressing care can quickly improve skin lesions and shorten hospitalization time. Clinically, different nursing models should be adopted according to the manifestations of skin lesions in different phases.